A Sociological Reading of EsmāʿIl FaṣIḥ’s Winter 62 Using Genetic Structuralism - Mahbood Fazeli; Fatemeh Mirzaei (Matn/Pizhūhī-i Adabī, 2020)
This article analyzes the novel Winter 62 by Esmāʿil Faṣiḥ using Lucien Goldmann's genetic structuralism approach. Based on genetic structuralism, the collective nature of literary works may be explained by the fact that the structure of these works corresponds to the mental structure of certain social groups. Therefore, the purpose of this study is to answer the following questions: How did Iranian society's political, social, and cultural structures influence the author's mental structures and the emergence of this novel during the 1980s? What is the relationship between these structures and the structure of the novel? According to this study, this novel is primarily a social work produced by an American-educated, urban middle-class author who emphasizes war's negative effects. By placing the narrator on the battlefield, the author reflects the views of the middle class on the social and political issues that were prevalent in Iranian society at that time. Winter 62 is the result of the conflicts. By examining one of the most important social themes, namely the war, Faṣiḥ illustrates the social structure that governed a period in Iranian history.